Chapter 16 The organic Internet as a resilient practice - Antoniadis, Panayotis (Taylor & Francis, 2019)
The idea that digital and physical space are increasingly interconnected, and that architecture and urban design should be conceptualised beyond buildings, streets and so on, is rather old and well understood. What is less clear is the fact that digital space is socially and politically 'produced' in similarly complex ways to the physical. It is thus subject to power structures, manipulation tactics, fundamental rights, borders and constraints, despite its perceived 'infiniteness'.